Comparative anatomy of chromosomal domains with imprinted and non-imprinted allele-specific DNA methylation. - Anupam Paliwal; Alexis M Temkin; Kristi Kerkel; Alexander Yale; Iveta Yotova; Natalia Drost; Simon Lax; Chia-Ling Nhan-Chang; Charles Powell; Alain Borczuk; Abraham Aviv; Ronald Wapner; et al. (PLoS Genetics, 2013)
Allele-specific DNA methylation (ASM) is well studied in imprinted domains, but this type of epigenetic asymmetry is actually found more commonly at non-imprinted loci, where the ASM is dictated not by parent-of-origin but instead by the local haplotype. We identified loci with strong ASM in human tissues from methylation-sensitive SNP array data. Two index regions (bisulfite PCR amplicons), one between the C3orf27 and RPN1 genes in chromosome band 3q21 and the other near the VTRNA2-1 vault RNA in band 5q31, proved to be new examples of imprinted DMRs (maternal alleles methylated) while a third, between STEAP3 and C2orf76 in chromosome band 2q14, showed non-imprinted haplotype-dependent ASM. Using long-read bisulfite sequencing (bis-seq) in 8 human tissues we found that in all 3 domains the ASM is restricted to single differentially methylated regions (DMRs), each less than 2kb. The ASM in the C3orf27-RPN1 intergenic region was placenta-specific and associated with allele-specific expression of a long non-coding RNA. Strikingly, the discrete DMRs in all 3 regions overlap with binding sites for the insulator protein CTCF, which we found selectively bound to the unmethylated allele of the STEAP3-C2orf76 DMR. Methylation mapping in two additional genes with non-imprinted haplotype-dependent ASM, ELK3 and CYP2A7, showed that the CYP2A7 DMR also overlaps a CTCF site. Thus, two features of imprinted domains, highly localized DMRs and allele-specific insulator occupancy by CTCF, can also be found in chromosomal domains with non-imprinted ASM. Arguing for biological importance, our analysis of published whole genome bis-seq data from hES cells revealed multiple genome-wide association study (GWAS) peaks near CTCF binding sites with ASM.